(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
‘Kanthapura’ is an excerpt from Raja Rao’s novel ‘Kanthapura’, appeared in 1938.The novel is about the days when Indians were struggling for independence under Mahatma Gandhi. The novel describes the events that take place in the Kanthapura under the impact of the Gandhi’s non –violence and non – co-operation movement in 1930’s. Kanthapura is a special novel for young generation of twenty first century, in more than one sense. It takes us back to the times when India as a Nation was fighting for independence. The novel narrates the long battle and how it was fought by the masses. Gandhi is a metaphorical presence in Kanthapura, an absent hero. It was Gandhi’s greatness that he produced thousands of little Gandhi throughout the country. Moorthy was one of them. Moorthy, a young student of Kanthapura is the central figure of the novel.